Self-infusion programmes for immunoglobulin replacement at home: feasibility, safety and efficacy. - Bhole, M; Burton, J; Chapel, H (2008)
This review of the currently available literature from more than two decades of clinical experience with self-infusions of immunoglobulin at home provides evidence to support the feasibility, safety, and efficacy in all age groups. Self-infusions at home not only increase patient confidence and their understanding of the immune deficiency but also contribute to the improvement of health-related quality of life. Such home therapy programs should be encouraged, and wherever possible, experienced centers should extend their services to include patients who require immunoglobulin therapy for immunomodulation. Home therapy programs play an important role in long-term health outcome.